Return sweeps in reading: Processing implications of undersweep-fixations - Slattery, TJ; Parker, AJ (Springer, 2019)
Models of eye-movement control during reading focus on reading single lines of text. However, with multiline texts, return sweeps, which bring fixation from the end of one line to the beginning of the next, occur regularly and influence ~20% of all reading fixations. Our understanding of return sweeps is still limited. One common feature of return sweeps is the prevalence of oculomotor errors. Return sweeps, often initially undershoot the start of the line. Corrective saccades then bring fixation closer to the line start. The fixation occurring between the undershoot and the corrective saccade (undersweep-fixation) has important theoretical implications for the serial nature of lexical processing during reading, as they occur on words ahead of the intended attentional target. Furthermore, since the attentional target of a return sweep will lie far outside the parafovea during the prior fixation, it cannot be lexically preprocessed during this prior fixation. We explore the implications of undersweep-fixations for ongoing processing and models of eye movements during reading by analysing two existing eye-movement data sets of multiline reading.